Teachers’ Perceptions of Speaking Confidence Strategies: A Case Study at Cambridge English School - Sulistiana Ulpa; Muhammad Tahir; Fatimah Hidayahni Amin (ELS Journal on Interdisciplinary Studies in Humanities, 2025)
In EFL (English as a Foreign Language) classrooms, many students struggle with speaking due to anxiety, low self-confidence, and fear of making mistakes. This issue is particularly prevalent among learners with limited vocabulary or basic proficiency levels, making it a persistent challenge for language teachers. This study explores teachers’ perceptions of the strategies they employ to build students’ speaking confidence in an EFL context. Conducted at Cambridge English School in Makassar, Indonesia, this qualitative research involved in-depth interviews and classroom observations of three experienced English teachers. Thematic analysis of the data revealed four key strategies perceived as effective: active learning (e.g., role-play and peer interviews), collaborative learning (especially small group discussions), praise and positive feedback, and creating safe peer-based environments. Teachers reported that these strategies increased students’ willingness to participate, enhanced their fluency, and encouraged risk-taking in communication. The emotional support provided through praise and structured peer collaboration helped reduce anxiety and fostered a sense of psychological safety. These findings are interpreted through theoretical lenses such as Vygotsky’s sociocultural theory, Krashen’s affective filter hypothesis, and Bandura’s self-efficacy theory. The study concludes that promoting speaking confidence in EFL learners requires not only linguistic input but also strategies that address emotional and social aspects of learning. Implications for learner-centered pedagogy are discussed.